2021
DOI: 10.3390/plants10020400
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cannabinoid Metabolites of Cannabis sativa L. with Therapeutic Potential

Abstract: The cannabis plant (Cannabis sativa L.) produces an estimated 545 chemical compounds of different biogenetic classes. In addition to economic value, many of these phytochemicals have medicinal and physiological activity. The plant is most popularly known for its two most-prominent and most-studied secondary metabolites—Δ9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD). Both Δ9-THC and CBD have a wide therapeutic window across many ailments and form part of a class of secondary metabolites called cannabino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 58 publications
3
33
0
Order By: Relevance
“…However, this study was intended to investigate the effect of the whole extract of Cannabis sativa L. on oxidative stress markers. The antioxidant activity of CBDA was found to be low in vitro, and thus it could be concluded that other compounds (flavonoids or/and terpenoids) in the extract also have an effect on oxidative stress markers, which corroborates literature data claiming that flavonoids and terpenoids have a wide therapeutic window [15].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, this study was intended to investigate the effect of the whole extract of Cannabis sativa L. on oxidative stress markers. The antioxidant activity of CBDA was found to be low in vitro, and thus it could be concluded that other compounds (flavonoids or/and terpenoids) in the extract also have an effect on oxidative stress markers, which corroborates literature data claiming that flavonoids and terpenoids have a wide therapeutic window [15].…”
Section: Discussionsupporting
confidence: 83%
“…Cannabis sativa L. produces multiple chemical compounds of different biogenetic classes [ 15 ], and many studies have demonstrated the antioxidant activity of Cannabis in vitro [ 19 , 22 ]. The phenolic compounds are mainly responsible for the antioxidant activity, while hemp seeds due to their active compounds, have health benefits such as lowering the cholesterol level in the blood or alleviating constipation and are also useful in the treatment of cardiovascular diseases [ 11 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several analytical methods, such as optical rotatory dispersion (ORD) and electronic circular dichroism (CD) based studies, liquid chromatography coupled to high resolution tandem mass spectrometry (LC - MS / MS), headspace solid phase microextraction (HS-SPME), overpressured layer chromatography (OPLC), high-performance thin-layer chromatography (HPTLC), high-performance liquid chromatography with diode array detector (HPLC-DAD), liquid chromatography with high resolution mass spectrometry (LC-HRMS), gas chromatography with flame ionization detector (GC-FID) and gas chromatography – mass spectrometry (GC–MS)-based qualitative and quantitative determination, nuclear magnetic resonance (NMR) and mass spectrometry (MS) based structural determination have played a critical role in phytochemical profiling of different medicinal and nontherapeutic cultivars ( Calvi et al, 2018 ). The content of tetrahydrocannabinol and cannabidiol in any cultivar is essentially important for its main prescribed and ‘legally safe’ recommendation ( Raderman, 2016 , Lowe et al, 2021 ). Therefore, commercially marketed cultivars must be studied for all possible types of synergistic interactions and chemical components present to determine the safe use of Cannabis as a useful medicinal herb ( Jin et al, 2017 ).…”
Section: Therapeutic Roles Of Phytochemical Constituents Of Cannabis Spmentioning
confidence: 99%
“…Caflanone, a secondary metabolite from non-cannabinoid extracts of C. sativa [ 183 ] inhibited a number of entry factors for human corona virus hCov-OC43, pro-inflammatory cytokines (IL-1β, IL-6, IL-8, Mip-1α, TNF-α), ABL-2, cathepsin L, PI4Kiiβ and AXL-2 [ 184 ]. TNF-α was reduced by THC in a mouse model of Staphylococcal enterotoxin-B (SEB)-mediated ARDS [ 185 ] and in human cell line in vitro models [ 173 ].…”
Section: Antiviral Activity: Special Focus On Sars-cov-2mentioning
confidence: 99%